Genesis of tramsmissible protein states via deformed templating - Makarava, Natallia (Landes Bioscience, 2012)
Prion replication occurs via a template-assisted mechanism, which postulates that the folding pattern of a newly recruited polypeptide chain accurately reproduces that of a template. The concept of prion-like template-assisted propagation of an abnormal protein conformation has been expanded to amyloidogenic proteins associated with Alzheimer, Parkinson, Huntington diseases, amyotrophic lateral sclerosis and others. Recent studies demonstrated that authentic PrP(Sc) and transmissible prion disease could be generated in wild type animals by inoculation of recombinant prion protein amyloid fibrils, which are structurally different from PrP(Sc) and lack any detectable PrP(Sc) particles. Here we discuss a new replication mechanism designated as “deformed templating,” according to which fibrils with one cross-β folding pattern can seed formation of fibrils or particles with a fundamentally different cross-β folding pattern. Transformation of cross-β folding pattern via deformed templating provides a mechanistic explanation behind genesis of transmissible protein states induced by amyloid fibrils that are considered to be non-infectious. We postulate that deformed templating is responsible for generating conformationally diverse amyloid populations, from which conformers that are fit to replicate in a particular cellular environment are selected. We propose that deformed templating represents an essential step in the evolution of transmissible protein states.